Sovereignty and national identity: the Panamanian perception of the canal and US foreign policy - Ortiz, Victor; Barsallo, Gabisel; Mendoza, Elisa; Yanis-Orobio, Rebeca (Frontiers in Political Science, 2025)
This article presents an analysis of President Trump's statements on the Panama Canal from the perspective of Mearsheimer's Offensive Realism, examining their impact on Panamanian national identity and perception of sovereignty complemented by Dependency Theory to account for Panama's position as a peripheral and dependent state. The research is based on statistical analysis of two public opinion surveys (n = 906, n = 732) conducted in February and April 2025, applying chi-square tests, correspondence analysis, and Spearman's correlation. Results reveal that Panamanians interpret these statements as a geopolitical strategy aimed at containing Chinese influence in the region, confirming Offensive Realism principles of power maximization and control of spheres of influence. Findings indicate that the Panama Canal is a symbol of Panamanian national identity and territorial sovereignty. The temporal analysis shows an evolution in public perception, where the narrative about the “Chinese threat” progressively lost credibility (p < 0.024), while identification with the Canal as a national symbol remained strong (Spearman's correlation = 0.591, p < 0.001). Provinces differed significantly in how they saw presidential comments and how the media handled information. Popular response based on historical memory and collective identity demonstrates national symbols used as defense mechanisms against external hegemonic pressures in the reconfiguration of the international order.